Analisis Ketersediaan dan Kebutuhan Air Serta Penentuan Pola Tanam pada Irigasi Air Palik Aur Gading Kabupaten Bengkulu Utara - Khairul Amri; Fepy Supriani; Serlinna Anggraini Darmo (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2023)
Air Palik Irrigation Area is located in Aur Gading Village, North Bengkulu Regency with a potential area of 1015 Ha with a functional area of 950 Ha. Climate change in Indonesia affects rainfall intensity, temperature, air pressure, humidity and water availability. Limited water availability will hamper the growth process for plants. Based on this, this research was conducted to determine the comparison of water needs and availability in the Air Palik Aur Gading irrigation area and the determination of cropping patterns. The methods used in this study include the aljabar average method to analyze rainfall, the F.J. Mock method to determine the value of water availability and 2 methods, including KP-01 and the CROPWAT 8.0 to determine the value of water demand used. The results showed that the maximum mainstay discharge occurred in November period 2 of 7.11 m3/second. The maximum irrigation water requirement in the KP-01 method was obtained at 3.12 liters/second/hectare which occurred in the first period of August while in the CROPWAT 8.0 method it was obtained at 1.16 liters/second/hectare which occurred in the third period of May. Keywords: Water Demand, Water Availability, Cropping Pattern, KP-01, Cropwat Software Version 8.0